2014
DOI: 10.3855/jidc.5393
|View full text |Cite
|
Sign up to set email alerts
|

Similarities between Salmonella Enteritidis isolated from humans and captive wild animals in South Africa

Abstract: Introduction: Salmonella is well recognized as an aetiological agent of gastrointestinal and diarrhoeal disease. Salmonella enterica serotype Enteritidis (Salmonella Enteritidis) is one of the commonest serotypes associated with foodborne illness. In South Africa, we compared Salmonella Enteritidis strains isolated from humans with gastroenteritis and strains isolated from captive wild animals, between June 2011 and July 2012. Methodology: Bacteria were phenotypically characterized using standard microbiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Three of the five studies found that NTS recovered from children and adults in some African settings were originated from human reservoirs despite NTS is commonly considered to be zoonotic and close contacts between humans and animals were observed (231)(232)(233). In contrast, two other studies found PFGE patterns of NTS isolates from wildlife and poultry were matched to or clustered with those isolated from children and adults, suggesting zoonotic transmission (234,235). On study further supported transmission from poultry by phage typing (235).…”
Section: Applications Of Microbial Subtypingmentioning
confidence: 81%
“…Three of the five studies found that NTS recovered from children and adults in some African settings were originated from human reservoirs despite NTS is commonly considered to be zoonotic and close contacts between humans and animals were observed (231)(232)(233). In contrast, two other studies found PFGE patterns of NTS isolates from wildlife and poultry were matched to or clustered with those isolated from children and adults, suggesting zoonotic transmission (234,235). On study further supported transmission from poultry by phage typing (235).…”
Section: Applications Of Microbial Subtypingmentioning
confidence: 81%
“…These findings fit with prior evidence of similar molecular profiles among S . Enteritidis strains collected from humans and chickens ( 22 ) and from humans and other animals ( 23 ). Our analyses also identified a close relationship between S .…”
Section: Discussionmentioning
confidence: 99%
“…Faeces are also routinely used to screen for pathogenic bacteria by standard microbiological techniques or molecular identification (Clostridium perfringens [47]; Rickettsia felis [48]; Salmonella enterica serovar. Enteritidis [49] and Typhimurium [50]; Mycobacterium bovis [51]), and nowadays, high-throughput metagenomic techniques allow us to characterise the whole gut microbial community composition at once including the pathogenic bacteria from a single faecal sample [52,53]. Of course, in a One Health context, faeces from wildlife can also be used to investigate antimicrobial resistance (AMR), either by screening for AMR genes through molecular methods, or by culture and phenotypical methods (e.g., [54] on Staphilococcus aureus in lemurs).…”
Section: Faecesmentioning
confidence: 99%